Major Histocompatibility Complex gene Polymorphism in Systemic Lupus Erythematosus Patients - Zahraa Haleem Alqaim1 , Methak J. Al-Jboori2 , Mona N. Al-Terehi3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The major histocompatibility complex (MIC) is one of the MHC class I related genes which related withautoimmune diseases , the present study aims to investigated association between MIC gene polymorphismclass I in systematic lupus erythrymatous patients within Hilla city, the present study implemented usingwhole blood genomic DNA and single strand DNA conformation polymorphism (SSCP) for detection genepolymorphisms and haplotypes frequency, The results of present study show that 183 bp of MIC gene and ithas three haplotypes (A, B, and C) each of these haplotypes consist of two bands, non-significant differencesbetween patient and control in haplotypes frequency, B haplotype was more frequent in patinas than others(20%) while A was more frequents in control than others (22.8%). The present study concluded that MICgene may be contributed in immune response of SLE and can be used in pre diagnosis of disease. This studywas one of the serious investigators deal with several immune genes in this disease in Iraqi SLE.